2023
DOI: 10.3390/coatings13050891
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Behavior of Doped DLC Coatings in the Presence of Ionic Liquid Additive under Different Lubrication Regimes

Abstract: Diamond-like carbon (DLC) coatings are widely used in industries that require high durability and wear resistance, and low friction. The unique characteristics of DLC coatings allow for the possibility of creating adsorption sites for lubricant additives through the doping process. In this study, the combined use of europium-doped diamond-like carbon (Eu-DLC), gadolinium-doped diamond-like carbon (Gd-DLC), and pure DLC coatings and an ionic liquid (IL) additive, namely, trihexyltetradecylphosphonium bis (2-eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 73 publications
2
25
0
Order By: Relevance
“…et.al. shows the similar results found in the optical microscopy images of different lubricant films along with SEM-EDS images, the wear reduction is clearly evident by using ionic liquids as additives and doping of DLC coatings [74].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…et.al. shows the similar results found in the optical microscopy images of different lubricant films along with SEM-EDS images, the wear reduction is clearly evident by using ionic liquids as additives and doping of DLC coatings [74].…”
Section: Discussionsupporting
confidence: 81%
“…A study performed by M Sadeghi. et.al. shows the similar results found in the optical microscopy images of different lubricant films along with SEM-EDS images, the wear reduction is clearly evident by using ionic liquids as additives and doping of DLC coatings [74]. The SEM-EDS technique was used to assess the impact of IL with 2.3% Gd-DLC and 2.4% Eu-DLC.…”
Section: Wear Mechanism Characterizationsupporting
confidence: 64%
See 2 more Smart Citations
“…While most published studies focused on doping and/or alloying a-C coatings with metals or metalloids, doping a-C films with rare-earth elements and rare-earth oxides , has only recently been explored. As one example, Omiya et al, Sadeghi et al, and Shaikh et al evaluated the tribological properties of gadolinium (Gd)- and europium (Eu)-alloyed a-C films deposited by high power impulse magnetron sputtering (HiPIMS) in the presence of synthetic oil containing a class of promising additives for transmission fluids, namely phosphonium phosphate ionic liquids. , The results of tribological experiments and scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS) measurements indicated that only the introduction of Gd in the a-C matrix favors the formation of a transfer layer on the steel counterbody that enhances the generation and adhesion of a lubricious and antiwear boundary layer (i.e., tribofilm) from the lubricant additives . As another example, Meng et al investigated the effect of the introduction of lanthanum (La) in DLC films grown by magnetron sputtering on the resulting mechanical, tribological, and wetting properties .…”
Section: Introductionmentioning
confidence: 99%